2018
DOI: 10.1002/2017jd027638
|View full text |Cite
|
Sign up to set email alerts
|

An Uncertainty Data Set for Passive Microwave Satellite Observations of Warm Cloud Liquid Water Path

Abstract: The first extended comprehensive data set of the retrieval uncertainties in passive microwave observations of cloud liquid water path (CLWP) for warm oceanic clouds has been created for practical use in climate applications. Four major sources of systematic errors were considered over the 9‐year record of the Advanced Microwave Scanning Radiometer‐EOS (AMSR‐E): clear‐sky bias, cloud‐rain partition (CRP) bias, cloud‐fraction‐dependent bias, and cloud temperature bias. Errors were estimated using a unique merged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…On the other hand, Genkova et al (2007) show that the ASTER infrared-window retrieval exhibits a low height bias of about 250 m on average compared to the more accurate stereo height retrieval, although the difference might have been caused by inadequate cloud motion correction in the stereo retrievals. In broken low-level cloud scenes, Greenwald et al (2018) found a 450-m low bias in MODIS Collection 6 CTHs compared to Cloud-Aerosol Lidar with Orthogonal Polarization layer top heights, which was attributed to the influence of the warm ocean surface on 1-km MODIS brightness temperatures in partly cloudy pixels. This potential warm surface effect, however, is likely to be much smaller in the 90-m ASTER brightness temperatures.…”
Section: Cloud Fraction Cth Cloud Spatial Distribution and Fractalmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Genkova et al (2007) show that the ASTER infrared-window retrieval exhibits a low height bias of about 250 m on average compared to the more accurate stereo height retrieval, although the difference might have been caused by inadequate cloud motion correction in the stereo retrievals. In broken low-level cloud scenes, Greenwald et al (2018) found a 450-m low bias in MODIS Collection 6 CTHs compared to Cloud-Aerosol Lidar with Orthogonal Polarization layer top heights, which was attributed to the influence of the warm ocean surface on 1-km MODIS brightness temperatures in partly cloudy pixels. This potential warm surface effect, however, is likely to be much smaller in the 90-m ASTER brightness temperatures.…”
Section: Cloud Fraction Cth Cloud Spatial Distribution and Fractalmentioning
confidence: 90%
“…In broken low‐level cloud scenes, Greenwald et al. () found a 450‐m low bias in MODIS Collection 6 CTHs compared to Cloud‐Aerosol Lidar with Orthogonal Polarization layer top heights, which was attributed to the influence of the warm ocean surface on 1‐km MODIS brightness temperatures in partly cloudy pixels. This potential warm surface effect, however, is likely to be much smaller in the 90‐m ASTER brightness temperatures.…”
Section: Statistical Overview Of Cloud Field Propertiesmentioning
confidence: 99%
“…While the Lebsock and Su () study uses an alternative CERES‐MODIS retrieval (Collection 5.1; Platnick et al, ) to the one used here and in Painemal et al (), the conclusions are likely to apply more broadly, given that both CERES‐MODIS retrievals produce comparable results in MBL clouds (Zhang et al, ). Greenwald et al () show that if a bias correction is applied to the satellite MWR retrieval accounting for precipitation‐related biases (among others), the LWP retrieved from satellite MWR is reduced and becomes more comparable to the lower water paths from MAGIC in broken cloud conditions.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…A shift of the distribution mode can be achieved by reducing the model's bulk condensate amount in the cumulus regime and increasing it in the stratocumulus regime, a change that is consistent with adjusting the model toward observed all-sky LWP values from the CERES-MODIS SSF retrieval. Given the recent insights from Lebsock and Su (2014) and Greenwald et al (2018) on precipitation-related biases from the satellite MWR retrievals, the CERES-MODIS SSF LWP therefore seems to the be the more appropriate reference choice here, despite the remaining uncertainties on the magnitude of the all-sky LWP.…”
Section: It Is Evident Frommentioning
confidence: 99%
See 1 more Smart Citation